2019
DOI: 10.1021/jacs.9b00146
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of Nucleotide Flipping in Enzyme Specificity Using 19F NMR

Abstract: A broad range of proteins employ nucleotide flipping to recognize specific sites in nucleic acids, including DNA glycosylases, which remove modified nucleobases to initiate base excision repair. Deamination, a pervasive mode of damage, typically generates lesions that are recognized by glycosylases as being foreign to DNA. However, deamination of 5-methylcytosine (mC) generates thymine, a canonical DNA base, presenting a challenge for damage recognition. Nevertheless, repair of mC deamination is important beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 92 publications
0
44
0
Order By: Relevance
“…How this enzyme knows the history of the nucleobase it interacts with is unknown. 42 A recent F-NMR study has shown that there may be a link between the sequence that is more prone to methylation, and a similar sequence that has been observed to interact favorably with TDG. 42 In any case, the enzyme differentiates between T in GT from the T in AT.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How this enzyme knows the history of the nucleobase it interacts with is unknown. 42 A recent F-NMR study has shown that there may be a link between the sequence that is more prone to methylation, and a similar sequence that has been observed to interact favorably with TDG. 42 In any case, the enzyme differentiates between T in GT from the T in AT.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 42 A recent F-NMR study has shown that there may be a link between the sequence that is more prone to methylation, and a similar sequence that has been observed to interact favorably with TDG. 42 In any case, the enzyme differentiates between T in GT from the T in AT. This observation suggests an important role for the WC partner of the base being flipped out.…”
Section: Results and Discussionmentioning
confidence: 99%
“…All described fluctuations of n max and n min after single 2 H/ 1 H replacement can result in DNA damage due to the slowdown in the rate of bubble forming (especially non-superhelical stress-induced denaturation bubbles having more than 4 base-pairs), including the promoter regions and binding points of specific proteins (e.g., DNA repair enzymes [41,55]), or because of the overwhelming rate of flipping-out DNA nucleobases that can be accompanied by increasing both the speed of modification of their chemical structure and mismatched protein-DNA interaction [56][57][58][59].…”
mentioning
confidence: 99%
“…Notably, the relatively high HB occupancy observed in S8 is in fact attributed to two adjacent G·C bps. The above results may provide the molecular explanations for the fact that TDG tends to target to the CpG-riched region ( 82 , 83 ).…”
Section: Resultsmentioning
confidence: 73%